(untitled) (Research, Society and Development, 2022)
The degradation of the environment by human action is a complex, collective, broad and multi-determined problem. Faced with legal, commercial, advertising and social demands, different organizations have faced the challenge of reconciling economic development and environmental preservation. The various notions and models of sustainability provide paths in this mission, especially the International Organization for Standardization - International Organization for Standardization - ISO 1400 and the Environmental Management Systems (EMS). In this context, Higher Education Institutions (HEIs) still face this issue in an incipient way, despite their social, environmental and academic responsibility. Aiming to present an environmental management project in a private HEI in the city of Piripiri (PI), it is asked, what is the environmental and financial impact of the unbridled consumption of water, electricity and disposable materials, as well as the inappropriate dumping of garbage? As a justification, it is observed that the implementation of the project implemented adaptations in the physical structure of the place and promoted educational campaigns related to the management of water, electricity, disposable materials and garbage. To structure the proposal, the Kaizen framework was used to organize a systematized and accessible panorama in the identification of difficulties, elaboration of actions and delineation of expected goals of the interventions.